PENGARUH KARAKTERISTIK PERUSAHAAN DAN TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA DI MASA PANDEMI COVID-19 (Studi Empiris pada Sektor Industri dan Sektor Properti Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Fathia Aulia Putri; Darsono Darsono (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of firm characteristics and corporate governance on earnings management during the Covid-19 pandemic. The company characteristics used in this study are firm size as measured by the natural logarithm of total assets, and liquidity as measured by the current ratio. Meanwhile, corporate governance is measured through institutional ownership (percentage of shares owned by institutions), the proportion of Independent commissioners in the board structure, and audit quality as measured by percentage by acquiring the most clients who use the selected KAP in the Industrial and Real Estate Property sectors.This research was conducted on industrial and real estate property sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2022. Data collection was carried out through observation of annual reports obtained from the official website owned by the company and Bloomberg FEB Undip as a source of financial report data. The sampling technique used the purposive sampling method, with a total sample of 106 companies or 256 observation data. The technique was analyzed using multiple linear regression with the Ordinary Least Squares (OLS) approach.The results showed that liquidity and institutional ownership had a positive and significant effect on earnings management practices, while firm size, Independent board of commissioners and audit dominant had no effect on earnings management. This study aims to provide input for companies, investors and regulators in understanding the factors that influence earnings management practices, especially on crisis situations such as the Covid-19 pandemic.